1991
DOI: 10.1159/000129137
|View full text |Cite
|
Sign up to set email alerts
|

A New Surgical Model of Acute Liver Failure in the Pig: Experimental Procedure and Analysis of Liver Injury

Abstract: In this research, the effects of portocaval shunt plus 70% partial hepatectomy were evaluated in 11 pigs. Hepatic coma and death from progressive liver failure occurred in 5 pigs between 14 and 64 h from surgery, whereas 3 pigs, which also showed symptoms of progressive liver failure, died of presumed gastric hemorrhage between 17 and 19 h after surgery. In 3 pigs, transient liver failure was followed by complete recovery, as judged by clinical, electroencephalographic and biochemical parameters. No case of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 8 publications
0
8
0
2
Order By: Relevance
“…Their findings suggested that portal congestion is not the cause of postoperative hyperamylasemia and that other factors, involving liver function and the extent of the resection, play a more important role. The present study used a modification of a previously described model of posthepatectomy liver failure [27]. The model combines major liver resection with ischemiareperfusion injury of a small liver remnant and invariably results in postoperative liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…Their findings suggested that portal congestion is not the cause of postoperative hyperamylasemia and that other factors, involving liver function and the extent of the resection, play a more important role. The present study used a modification of a previously described model of posthepatectomy liver failure [27]. The model combines major liver resection with ischemiareperfusion injury of a small liver remnant and invariably results in postoperative liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…To create a partly reversible FHF model with limited survival by means of partial hepatectomy, 85-89% of the liver is removed. An alternative is a combined model of a less extensive partial hepatectomy supplemented with a liver toxin like galactosamine (19) or acetaminophen, or shunting of the portal (20,21) or arterial blood supply to bypass the remnant liver.…”
Section: Hepatic Failure Treated By a Microgravity-based Bioartificiamentioning
confidence: 99%
“…Most models maintain blood pressure when possible by means of fluids and inotropic support. The criteria for temperature 12 Olafsson et al 13 Tonnesen 15 Rozga et al 17 Filipponi et al 69 Hanid et al 16 De control, however, are less well defined. Olafsson et al 13 controlled temperature at 37.5ЊC Ϯ 5.0ЊC, whereas Nyberg et al 14 stipulated a more controlled range of 36ЊC to 37ЊC.…”
Section: Devascularized Modelsmentioning
confidence: 99%